2017
DOI: 10.1021/acs.inorgchem.7b00311
|View full text |Cite|
|
Sign up to set email alerts
|

Luminescent Zn(II) Coordination Polymers for Highly Selective Sensing of Cr(III) and Cr(VI) in Water

Abstract: Three photoluminescent zinc coordination polymers (CPs), {[Zn(tpeb)(2,5-tdc)(2,5-Htdc)]·2HO} (1), {[Zn(tpeb)(1,4-ndc)(1,4-Hndc)]·2.6HO} (2), and {[Zn(tpeb)(2,3-ndc)]·HO} (3) (tpeb = 1,3,5-tri-4-pyridyl-1,2-ethenylbenzene, 2,5-tdc = 2,5-thiophenedicarboxylic acid, 1,4-ndc = 1,4-naphthalenedicarboxylic acid, and 2,3-ndc = 2,3-naphthalenedicarboxylic acid) were prepared from reactions of Zn(NO)·6HO with tpeb and 2,5-Htdc, 1,4-Hndc, or 2,3-Hndc under solvothermal conditions. Compound 1 has a two-dimensional (2D) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(101 citation statements)
references
References 79 publications
2
99
0
Order By: Relevance
“…The quenching efficiency for various nitroaromatics were plotted in Figure . The detection limit of the Zn‐MOF as a luminescent probe for detecting NPLR solution was found to be 1.71 ppb, which is supported by the calculated results based on the equation: detection limit = 3δ/k (δ is the standard deviation of blank measurement; k is the slope between the luminescence intensity vs. log[NPLR] (Figure ). Bappaditya Gole et al had synthesized several MOFs to sense TNT as a level as 3.63 ppb .…”
Section: Resultsmentioning
confidence: 99%
“…The quenching efficiency for various nitroaromatics were plotted in Figure . The detection limit of the Zn‐MOF as a luminescent probe for detecting NPLR solution was found to be 1.71 ppb, which is supported by the calculated results based on the equation: detection limit = 3δ/k (δ is the standard deviation of blank measurement; k is the slope between the luminescence intensity vs. log[NPLR] (Figure ). Bappaditya Gole et al had synthesized several MOFs to sense TNT as a level as 3.63 ppb .…”
Section: Resultsmentioning
confidence: 99%
“…To check whether the energy‐transfer caused the observed quenching effect, we performed an experiment of simplified fluorescent analysis (Figure a) . The suspension of 1 in water was placed in a quartz cell (position B), while the solution of Cr 2 O 7 2− (1×10 −2 M) or CrO 4 2− (1×10 −2 M) was placed in the excitation path (position A) and emission path (position C), then we detected the fluorescence intensity.…”
Section: Resultsmentioning
confidence: 99%
“…[16] The PXRD patterns display that complexes 1-3 have almost no change before and after immersed in Cr 2 O 7 2À or MnO 4 À ,a nd the weights after the treatment of DMF/DMA( complex 1 in DMF and complex 2 or 3 in DMA, respectively) were characterizeda nd the results showed that there were almost no loss of the mass, [29] which implying that the main framework structures of 1-3 stillm aintain (Figure S5 a-S7). Both Cr 2 O 7 2À and MnO 4 À have wide absorption bands in the UV-vis area, [30,31] and there is overlap betweent he absorption bands of Cr 2 O 7 2À /MnO 4 À and the excitation of 1-3, which implying that Cr 2 O 7 2À /MnO 4 À may conceal the absorption of excitation energy and give rise to the fluorescence quenching. In addition, the interactions between anions and complexes may also lead to the quenching effect.…”
Section: àmentioning
confidence: 99%